Impact of TV terrorism news on Egyptians' perception of national security measures and civil liberties: A cultivation study - Salem, Reham Gamal (AUC Knowledge Fountain, 2016)
This study aims at examining the role of terrorism-related TV news content in cultivating terrorism risk perceptions among Egyptians in the aftermath of the June 30, 2013 events. The study also attempts to explore in-depth how and why terrorism threat perceptions correlate with the Egyptian people’s tolerance for more restrictive government measures regarding privacy and security. Previous studies found that heavy exposure to terrorism-related news can breed threat perception and fear of victimization. Further, citizens who feel under threat tend to be more willing to trade off their civil liberties. In this sense, the theoretical framework of this study is the Cultivation theory. The researcher employed the qualitative research method, involving twenty in-depth interviews conducted with expert and non-expert participants. According to the findings of this study, most of the research participants are light viewers who are affected by terrorism. The study also found that most research participants trust the official statements regarding the level of terrorism and the endorsed security-oriented measures. Based on this, participants expressed their willingness to compromise their civil liberties under the threat of terrorism.